Analisis Pengendalian Waktu dan Biaya dengan Metode Critical Path Method pada Perbaikan Peningkatan Jalan Bentot – Pasar Panas (MYC II) Kabupaten Barito Timur - Charles Charles (Jurnal Teknologi Berkelanjutan, 2025)
Road construction is essential to fulfill the human need to travel safely and easily from one place to another. Therefore, every region must have adequate road infrastructure, including East Barito Regency. To meet the demands for the development of the Bentot - Pasar Panas (MYC II) road network in East Barito Regency, this construction project aims to improve relevance and competitiveness by upgrading physical facilities and infrastructure. This study aims to formulate the critical path network for the Bentot - Pasar Panas (MYC II) road improvement project in East Barito Regency and to analyze the comparison of time and cost before and after project acceleration using the Critical Path Method. The research utilized the Critical Path Method (CPM). The results indicate that the critical path of the project consists of Mobilization, Management and Safety, and Thermoplastic Road Marking works. Furthermore, the initial cost of the project was Rp 29,851,000,000.00 with a duration of 390 calendar days. After implementing the crashing method, the total project cost became Rp 29,854,777,477.04, incurring an additional crashing cost of Rp 3,777,477.04, while the project duration was reduced to 334 days.